Improving the understanding and use of Technopreneurship in running Temanggung Coffee MSME Business - Mardinawati - Mardinawati; Sandi - Supaya; Sumanto - Sumanto; Kurniani - Kurniani; Rif'ah Dwi Astuti (Politeknik Negeri Semarang, 2022)
The problem in this research is how well the understanding, and ability to use technopreneurship in running a business. Data collection methods used in this research are survey and interview methods. Respondents consist of owners and managers of Temanggung coffee SMEs whose products have been included in district or city level exhibitions. Likert scale with gradation from strongly agree to strongly disagree is used to measure the assessment of respondents' opinions about the statements in the questionnaire. Respondents' answers were scored and analyzed using the average, maximum, minimum, sort, and criterion values. The conclusion of this study is the understanding and use of technopreneurship in running a business is in the good and very good intervals, and can still be improved to be very good. Understanding and ability to market the product has the best criteria value. Understanding and ability to use in managing operating capital and a strong internet signal are prioritized in increasing the understanding and use of technopreneurship